Bahasa Inggris - Ruslan Gunibala; Adnan Malaha; Astria lolo (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Creatinine is a kind of chemical in the body indicating damage to body cells. The levels in the blood indicate how much damage to body cells. The purpose of this study was to determine the description of serum creatinine levels in traditional gold mining workers in East Mamunga'a Village in 2021.This research is descriptive with a quantitative approach. The population in this study were all traditional gold mining workers with a total sample of 35 people. The sampling method used Accidental Sampling. The examination of serum creatinine levels using the Jaffe Reaction method and measured using a Spectrophotometer biosystem BTS 350. The types of data used were primary data and secondary data with data sourced from interviews and documentation. Furthermore, the data were analyzed univariate.The results show that 15 samples (42.9%) of serum creatinine are abnormal and 20 samples (57.1%) are normal. Serum creatinine levels that do not increase or are declared normal are caused by traditional gold mining workers adopting a healthy lifestyle. The conclusion is that traditional gold mining workers experience an increase in serum creatinine levels less than normal. The need to maintain a healthy lifestyle such as adequate rest during mining activities, consuming mineral water, and not consuming excessive supplements so as not to increase serum creatinine levels.